The effect of physical exertion training using a vertimax device in developing the characteristic strength with speed and the skill of shooting by jumping in front - high with the hand ball for youth - م.م هديل طالب محمد أ.د سهاد قاسم الموسوي (الرياضة المعاصرة)
The research problem has crystallized and in light of these capabilities, the level of performance depends on the application of modern training methods based on actual experimentation, and those methods aim to develop the components of achievement in this competition, including the quantities of exerting the distinctive strength with speed for the arms and feet, which reflects on good skillful performance because the skill of shooting by jumping forward and high forms A major role in achieving goals during the competition that qualifies the team to win, and through the follow-up of the researcher in the field and academic field, I noticed that there is a weakness in some physical abilities, which affects performance and skill level during training, so the researcher decided to use the scientific method (vertimax device through which The quantities of rapid force that each player exerts during the performance that must be employed to serve the nature of the physical and technical performance and determine the accuracy of correction towards the target, the goal of the research is to prepare and identify physical exertion exercises using a vertimax device in developing the characteristic strength with speed and the skill of shooting by jumping in front of - high with a ball The hand is for youth, and the researcher adopted the experimental approach by designing the two equal experimental and control groups. The research was conducted, and the research community was identified with handball players (Specialized School for Giftedness of the Ministry of Youth and Sports) with ages (14-15) years for the 2019 training season, which numbered 16 for the player, and physical exertion exercises were applied using a vertimax device on the experimental group for a period of eight weeks. With three training units per week, the researcher used the statistical bag (spss) to process the data, and the researcher reached the most important conclusions. The results were a remarkable development between pre and post measurement in developing the characteristic force of speed and the skill of shooting by jumping in front of the handball youth for the experimental group and for the benefit of telemetry